Effect of Sr Incorporation and Ni Exsolution on Coke Resistance of the Ni/Sr−Al2O3 Catalyst for Dry Reforming of Methane - Kim, Jeongmin; Seo, Jeong Cheol; Jang, Won Jun; Lee, Kyubock (ACS Sustainable Chemistry and Engineering, 2023)
The effects of Sr incorporation over Ni/Al2O3 catalysts were explored for the dry reforming of methane (DRM). Ni-exsolved catalysts (NiEXS) and conventional Ni-impregnated catalysts (NiIMP) were prepared by using a spray-pyrolysis-assisted evaporation-induced self-assembly (EISA) method to produce a solid solution and mesoporous structures. In the DRM tests, strontium showed crucial effects for improving the resistance of carbon formation and the stability of the catalyst. Particularly, NiEXS/ Sr−Al demonstrated a crystal size growth of 0.8% and a coking rate of 0.012 gc·gcat −1·h−1, which was remarkably lower than those of the other catalysts (NiIMP/Al, NiIMP/Sr−Al, and NiEXS/Al). This study primarily investigated the catalytic properties and strong metal− support interaction, which depended on the preparation procedure, for verifying the origin of the most stable NiEXS/Sr−Al catalyst. In particular, the roles of promotional Sr in enhancing the CO2 adsorption/desorption ability of the catalyst at different temperatures as well as the amount of oxygen species were elucidated in detail.
Keywords: Coke resistances; Dry reforming-of-methane; Evaporation induced self assemblies; Exsolution; Impregnated catalysts; Ni exsolution; Self-assembly method; Sr incorporation; Strong metal-support interaction; ]+ catalyst; coke resistance; dry reforming of methane; Ni exsolution; NiAl2O3; Sr incorporation; strong metal−support interaction